Universal Design for Learning (UDL) in the Academic Library: A Methodology for Mapping Multiple Means of Representation in Library Tutorials - Webb, Katy Kavanagh; Hoover, Jeanne K. (My University, 2015)
Librarians designed a biology tutorial not only to address an assignment, but also to make tutorials more accessible to students with various learning styles. The Science Librarian created the content by using aspects of the Information Literacy Standards for Science and Technology/Engineering, an informal survey of biology faculty, and assignments for the biology labs. The Instructional Design Librarian created multiple modules that engaged users through text, images, audio, and interactive tutorials. The researchers used Universal Design for Learning principles to address multiple learning styles, specifically multiple means of representation, and created a mapping technique for those principles that can be applied to any library tutorial. To assess the effectiveness, students with learning disabilities completed a usability test on the tutorial.